From early sexual debut to later overweight and obesity: a multilevel analysis of Ghanaian women - Joshua Okyere; Castro Ayebeng; Kwamena Sekyi Dickson; Precious Adade Duodu (Tropical Medicine and Health)
Abstract Background Beyond the socio-demographic and lifestyle factors, it is imperative to understand how early-life factors contribute to the development of overweight and obesity. One of such early-life factors is early sexual debut defined as first sexual intercourse before age 16. The study examines the association between early sexual debut and women’s risk of overweight/obesity in Ghana using a nationally representative data. Methods Data from the 2022 Ghana Demographic and Health survey was used. We analyzed the data of 6,478 women aged 16–49 years. The outcome variable was obesity status which was computed using the body mass index. The main explanatory variable was early sexual debut. We utilized multilevel logistic regression models to examine the association between early sexual debut and women’s risk of overweight/obesity, controlling for both individual (age, education, internet use, parity, wealth index, anemia status) and community level (residence and ecological zone) confounders. Results An estimated 3,183 (48.8% [95% CI 46.9–50.6]) were overweight/obese while 11.7% experienced early sexual debut. After adjusting for individual and community level factors, we found that women with an early sexual debut had a 25% higher likelihood of being overweight or obese compared to those without early sexual debut [AOR = 1.25; 95% CI 1.04–1.51]. The significant confounders associated with higher odds of obesity were increasing age, higher educational level, higher wealth index, parity, and frequent use of the internet. Rural residence and residence in the savannah ecological zone were associated with lower odds. Conclusion This study suggests that early sexual debut, a key life course event, may be linked to long-term health consequences including higher risk of overweight/obesity. The results underscore the importance of addressing early-life factors in the prevention of obesity. Public health interventions aimed at delaying sexual initiation could be vital in mitigating the growing burden of obesity in Ghana.